2020
DOI: 10.1007/s42729-020-00373-0
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost Application in Different Intercropping Patterns Improves the Mineral Nutrient Uptake and Essential Oil Compositions of Sweet Basil (Ocimum basilicum L.)

Abstract: Only a few studies have hitherto investigated the effects of the application of organic fertilizers in intercropping systems on the plant essential oil (EO) productivity. Hence, this work has aimed to study the effect of different intercropping patterns on EO quality and quantity of sweet basil (Ocimum basilicum L.) under vermicompost application. In the present study, the cropping patterns consisted of 1B:1CB, 2B:2CB, 3B:2CB, and 4B:2CB (basil: common bean) as well as the pure culture of both crops and fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 38 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Intercropping can increase sustainable production and reduce chemical inputs in agricultural systems 12 14 , establish an ecological balance, exploit resources to a greater extent, increase yields quantitatively and qualitatively, and decrease the damage caused by pests, diseases, and weeds 15 , 16 . Therefore, reducing farmer reliance on pesticides while at the same time maintaining crop productivity and quality are key intercropping goals for sustainable farming.…”
Section: Introductionmentioning
confidence: 99%
“…Intercropping can increase sustainable production and reduce chemical inputs in agricultural systems 12 14 , establish an ecological balance, exploit resources to a greater extent, increase yields quantitatively and qualitatively, and decrease the damage caused by pests, diseases, and weeds 15 , 16 . Therefore, reducing farmer reliance on pesticides while at the same time maintaining crop productivity and quality are key intercropping goals for sustainable farming.…”
Section: Introductionmentioning
confidence: 99%
“…Intercropping systems can also improve EO quantity and quality of medicinal plants, such as fennel ( Foeniculum vulgare Mill. ), dragonhead ( Dracocephalum moldavica L.), and sweet basil ( Ocimum basilicum L.) (Amani Machiani et al, 2019; Rezaei‐Chiyaneh, Amani Machiani, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the LER value >1 implies that the inter‐species competition is also less intense than the intra‐species competition. Similarly, previous studies showed that the use of environmental resources via both functional complementarity and facilitation in the intercropping system and yield improvements led to an increase in the LER (Fallah et al, 2018; Rezaei‐Chiyaneh, Amani Machiani, et al, 2020; Vafadar‐Yengeje et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…On‐the‐other‐hand, the higher content of DEO induced by fertilization is related to the role of the nutrients, especially N, in the development and division of new cells secreting DEO, secretory channels, and glandular trichomes (Fallah et al, 2018; Schuurink & Tissier, 2020). To improve the chemical composition of DEO of medicinal plants, we recommend the use of organic fertilizers in the intercropping system (Rezaei‐Chiyaneh, Amani Machiani, Javanmard, Maggi, & Morshedloo, 2020).…”
Section: Discussionmentioning
confidence: 99%